If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z(z) + 20z = 0 Multiply z * z 2z2 + 20z = 0 Reorder the terms: 20z + 2z2 = 0 Solving 20z + 2z2 = 0 Solving for variable 'z'. Factor out the Greatest Common Factor (GCF), '2z'. 2z(10 + z) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'z' equal to zero and attempt to solve: Simplifying z = 0 Solving z = 0 Move all terms containing z to the left, all other terms to the right. Simplifying z = 0Subproblem 2
Set the factor '(10 + z)' equal to zero and attempt to solve: Simplifying 10 + z = 0 Solving 10 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + z = 0 + -10 Combine like terms: 10 + -10 = 0 0 + z = 0 + -10 z = 0 + -10 Combine like terms: 0 + -10 = -10 z = -10 Simplifying z = -10Solution
z = {0, -10}
| 3+25x=2-0x+12 | | 34+(25x)+(35x)=93 | | 34+(25x)+(35x)=94 | | (1+i)*z*z+2iz-1=0 | | 34+(25x)+(35x)=90 | | 34(25x)(35x)=90 | | 2z+20z=o | | 55-3x=6-10x | | 4x+15=-5x-12 | | 2x-5+57=3x+9 | | 5y+6-9y= | | 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 | | 3r^2=-45 | | cos(c)+3*sin(c)=2 | | x=22y+39x | | 4x-5=6x+23 | | Log[2](3x+8)=5 | | 3x-2=-5x-6 | | -h^2+15h+50=0 | | -61= | | Y^2=5Y+50 | | 89=28-r | | 36=-3(-9-3z) | | 33x+117=14.5x | | 6x^3-4x-16x=0 | | 89=21-r | | 12=-8p+11+9p | | 1.5x+10=2x+20 |